Crime against maids: an evaluation of Shariah and civil law punishment - Ali Mohamed, Ashgar Ali; Amuda, Yusuff Jelili (Ontario International Development Agency, 2011)
It is undeniable facts that many maids whom have been abused sexually, physically, mentally, and psychologically by their employers or employer’s family or relative. Therefore, this study examines how Shari’ah punishment can be applied as a deterrent punishment and lesson to others. It is individual rights to work as employee based on his or her class, status, and educational career. Shari’ah is the only law that gives all rights to human being regardless of his or her status, gender, tribe, and religion. The study will apply quantitative and qualitative methods for the analysis. Questionnaire and interviewed would be conducted on subject matter in order to discover undocumented facts. The sample would be conducted in certain universities such as UPSI, IIUM, and UKM in Malaysia. This survey or data will be sampled as an empirical evidence and proof that many maids were sexually abused while some were inflicted with injuries. Globally, maids’ abuse is very serious and complex and it needs deterrent punishment to reduce high percentage of criminal against maids. The study also aims to discover the effectiveness of the Shari’ah to serve as best law to secure maids rights and protect them in working places. Finally, useful solution to outstanding problem and suggestions would be suggested in the findings.